(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
this article gives information about minister of Turkestan Nasirkhan Tora Kamolkhan Toraev and last days of his life. It is said that among the hundreds of patriots who battled for the Great Motherland known as Turkestan and lost their lives defending the independence of their people and nation, Nasirkhan Tora Kamolkhan Toraev’s name deserves particular recognition. Through his many endeavors, this breed - one of the greatest religious academics and political figures - proved that he is the progenitor of Turkestan.